Concomitant occurrence of multicentric hemangiosarcoma and histiocytic sarcoma in a dog - Gouveia, Bethânia Almeida [UNESP]; Perossi, Isabela Fernanda Spinelli [UNESP]; da Silva, Marina Carla Bezerra [UNESP]; Martinelli, Paulo Edson Baptista [UNESP]; Ramos, Fernanda Ramalho [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP] (Brazilian Journal of Veterinary Pathology, 2023)
Histiocytic sarcoma (HS) is uncommon malignant neoplasia of round cells with marked predilection in Rottweiler and Bernese Mountain. The disseminated form, which mainly affects the spleen, lungs, lymph nodes, bone marrow, skin, and subcutis, presents a quick and aggressive clinical behavior. Hemangiosarcoma (HAS) is a malignant neoplasm of endothelial vessel cells commonly reported to affect the right atrium of dogs’ hearts. A male Rottweiler, five years old, presented flaccid paraplegia and progressive muscular atrophy in the temporal, masseter, and limbs muscles; Due to the clinical stage of the animal, euthanasia was conducted. During the necroscopic examination, it was noticed that several masses presented different sizes; some were whitish, and others were reddish and spread in multiple organs (lungs, heart, spleen, stomach, kidneys, brain, medulla, skeletal muscle, and pre-scapular lymph node). Microscopically, in some organs such as the stomach, right ventricle, lungs, and medulla, it was noticed a proliferation of myeloid cells, highly cellular, with poor demarcation, no encapsulation, and with the infiltrative growth pattern of cells with high pleomorphism. Numerous tumoral emboli were observed in the spleen, brain, skeletal muscle, and lymph node. These cells were submitted for immunohistochemistry and were positive for CD18 (HS antibody). In the right atrium, liver, and kidney it was observed malignant and infiltrative endothelial proliferation (HSA) and emboli in the medulla. Therefore, we conclude that both neoplasms (HS and HSA) cause the animal’s paraplegia due to their embolism and metastasis to the spinal cord and skeletal muscle.
Keywords: mesenchymal neoplasia. paraplegic; metastasis; round cells